Shakespeare’s Romeo and Juliet tragedy as a content-based EFL class practices to reinforce and cement the EFL learners’ writing creativity and skill - MAOUCHE, Salima (Université de M'sila, 2017)
Shakespeare is undoubtedly the most famous British poet and playwright that human cultures and civilizations have ever witnessed. Although apprehended because of his complex language style, his imaginations and the harsh and rigid messages through the characters of his writings, we can however consider him as the most direct and the most reflecting playwright of human kind. He succeeded to depict the societal wounds whatever their nature was and thus teach a wealth generation about common sense, responsibility, love and determination. Furthermore, the language used, the linguistic features present in his works are therefore, a treasure bank for English language teachers and learners. However, his works are often avoided by EFL teachers as they deem it too complex for their students especially when English is taught and learnt as a foreign language. Shakespeare est sans aucun doute le poète et dramaturge britannique le plus célèbre que les cultures et les civilisations humaines ont jamais vu. Bien qu'il soit appréhendé en raison de son style de langue complexe, de son imagination et des messages rigoureux à travers les personnages de ses écrits, nous pouvons cependant le considérer comme le dramaturge le plus direct et le plus réfléchi du genre humain. Il a réussi à décrire les blessures sociétales quelle que soit leur nature et à enseigner ainsi une génération de richesse sur le bon sens, la responsabilité, l'amour et la détermination. En outre, la langue utilisée, les caractéristiques linguistiques présentés dans ses oeuvres sont donc une banque de trésorerie pour les enseignants et apprenants d'anglais.
Keywords: Shakespeare, playwright, societal wounds, Romeo and Juliet, Content based ( Shakespeare, dramaturge, blessures sociétales, Romeo et Juliette, classe FLE basée sur le contenu. EFL class )